Heme oxygenase up-regulation under ultraviolet-B radiation is not epigenetically restricted and involves specific stress-related transcriptions factors - Santa Cruz, Diego Mario (2017)
Heme oxygenase-1 (HO-1) plays a protective role against oxidative stress in plants. The mechanisms regulating its expression, however, remain unclear. Here we studied the methylation state of a GC rich HO-1 promoter region and the expression of several stress-related transcription factors (TFs) in soybean plants subjected to ultraviolet-B (UV-B) radiation. Genomic DNA and total RNA were isolated from leaves of plants irradiated with 7.5 and 15 kJ m-2 UV-B. A 304 bp HO-1 promoter region was amplified by PCR from sodium bisulfite-treated DNA, cloned into pGEMT plasmid vector and evaluated by DNA sequencing. Bisulfite sequencing analysis showed similar HO-1 promoter methylation levels in control and UV-B-treated plants (C: 3.4±1.3%; 7.5: 2.6±0.5%; 15: 3.1±1.1%). Interestingly, HO-1 promoter was strongly unmethylated in control plants. Quantitative RT-PCR analysis of TFs showed that GmMYB177, GmMYBJ6, GmWRKY21, GmNAC11, GmNAC20 and GmGT2A but not GmWRK13 and GmDREB were induced by UV-B radiation. The expression of several TFs was also enhanced by hemin, a potent and specific HO inducer, inferring that they may mediate HO-1 up-regulation. These results suggest that soybean HO-1 gene expression is not epigenetically regulated. Moreover, the low level of HO-1 promoter methylation suggests that this antioxidant enzyme can rapidly respond to environmental stress. Finally, this study has identified some stress-related TFs involved in HO-1 up-regulation under UV-B radiation.